2015
DOI: 10.4161/15384101.2014.985031
|View full text |Cite
|
Sign up to set email alerts
|

E2F1 and E2F2 induction in response to DNA damage preserves genomic stability in neuronal cells

Abstract: Abbreviations: ODN, oligodeoxynucleotide; NCS, neocarzinostatin; ASCAT, CAT antisense; ASE2F1, E2F1 antisense; ASE2F2, E2F2 antisense; wt E2F DO, wild-type E2F decoy oligodeoxynucleotide; mut E2F DO, mutant E2F decoy oligodeoxynucleotide.E2F transcription factors regulate a wide range of biological processes, including the cellular response to DNA damage. In the present study, we examined whether E2F family members are transcriptionally induced following treatment with several genotoxic agents, and have a role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 67 publications
2
21
0
Order By: Relevance
“…Similarly, AKT3 may be an important target gene of miRNA-195. From the functions annotated in the genes E2F1 and E2F2 in GO, we can speculate that the genes E2F1 and E2F2 are present on the nucleoplasm, and participate in the lens fiber cell apoptosis process or intrinsic apoptotic signaling pathway by p53 class mediator by forming a complex with a certain protein or transcription factor activity, sequence-specific DNA binding, which is consistent with the results reported previously (Castillo et al, 2015). In addition, PI3K-Akt and AMPK are reported to be positive and negative regulators of mTOR activity, respectively, and mTOR is a well-known sensor for extracellular nutrients and growth factors, which converges many key signals and is widely involved in cell cycle, cell proliferation, and cellular metabolic processes, and has important biological roles in regulating apoptosis, physiological, and pathological processes (Ciuffreda et al, 2010).…”
Section: Functional Analysissupporting
confidence: 91%
“…Similarly, AKT3 may be an important target gene of miRNA-195. From the functions annotated in the genes E2F1 and E2F2 in GO, we can speculate that the genes E2F1 and E2F2 are present on the nucleoplasm, and participate in the lens fiber cell apoptosis process or intrinsic apoptotic signaling pathway by p53 class mediator by forming a complex with a certain protein or transcription factor activity, sequence-specific DNA binding, which is consistent with the results reported previously (Castillo et al, 2015). In addition, PI3K-Akt and AMPK are reported to be positive and negative regulators of mTOR activity, respectively, and mTOR is a well-known sensor for extracellular nutrients and growth factors, which converges many key signals and is widely involved in cell cycle, cell proliferation, and cellular metabolic processes, and has important biological roles in regulating apoptosis, physiological, and pathological processes (Ciuffreda et al, 2010).…”
Section: Functional Analysissupporting
confidence: 91%
“…This phenomenon seems to be cell context dependent and may play a role in neurodegeneration (51). Furthermore, E2f2 and E2F1 were reported to provide genomic stability in some neurons in the context of DNA damage (52). This study additionally showed accumulation of E2f2 protein levels, despite unchanged transcription.…”
Section: Discussionsupporting
confidence: 54%
“…The role of E2fs in mitosis has been shown in cancer cells [5963]. Although the specific function of E2f2 in response to radiation has not been studied, E2f2 transcript and protein levels increase in response to genotoxic stress and maintain genomic stability in neuronal cells [64]. Why E2f2 shows bi-directional expression changes, whereas other E2f members (i.e., E2f1 , E2f3 , E2f4 , and E2f8 ) do not, is currently not known.…”
Section: Discussionmentioning
confidence: 99%